Pengaruh Penerapan Kode Etik Akuntan terhadap Kualitas Audit dan Akuntabilitas Profesional - Nur Imroatus Sholikah; Adinda Nibros Zahira Fasya; Tries Ellia Sandari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the effect of the implementation of the code of ethics for accountants on audit quality and professional accountability. Audit quality is greatly influenced by the application of ethical principles, such as integrity, objectivity, competence, and independence, which form the basis for auditors in carrying out their duties. The research method used a qualitative approach with documentary analysis, exploring secondary data from official documents related to the implementation of the code of ethics and audit practices. The results show that consistent implementation of the code of ethics has a positive effect on audit quality, as it encourages auditors to act objectively, independently, and professionally. In addition, auditor accountability increases in line with compliance with the code of ethics, which strengthens the credibility of audit results. In conclusion, the implementation of a good code of ethics not only improves audit quality but also strengthens the professional accountability of auditors, thereby reinforcing public confidence in audited financial statements.